Rancang Bangun Sistem Pemantauan Suhu dan Kelembapan pada Mesin Tetas Telur Penyu Berbasis IoT Di Penangkaran Penyu Batu Hiu Pangandaran - Nivika Tiffany Somantri; Yuda Bakti Zainal; Wibisana Nugraha; M. Reza Hidayat; Dede Furqon Nurjaman; Naftalin Winanti (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
Chelonioidea or Sea turtle is an animal that is currently on the verge of extinction. Smart THEM prototype is designed to be able to maintain temperature of the sand medium in male mode (27–29oC) and female (29–32oC) using DS18B20 temperature sensor, and maintain the humidity of the sand medium (37.5%–50.2 %) using a capacitive soil moisture sensor with an indicator of the remaining water in the tank using an ultrasonic sensor. Turtle eggs incubated at high temperatures will give birth to female turtles, and at low temperatures, male turtles. This tool also utilizes internet networks for remote monitoring through the Blynk application by using a Mega+Wi-Fi microcontroller. In the test, Smart THEM is able to maintain the temperature in the male mode, which is 27.87–28.19 0C, and in the female mode, which is 30.19–30.31oC. Smart THEM is also able to maintain humidity between 45%-48%. The response time needed to increase temperature by 0.5oC is 20 minutes, and the humidity by 20% is 3 seconds. Blynk application is able to acquire temperature and humidity, and remaining water data in the tank from Smart THEM via internet.